Targeting Cancer Cells with BET Bromodomain Inhibitors - Xu, Yali (Cold Spring Harb Perspect Med, 2017)
Cancer cells are often hypersensitive to the targeting of transcriptional regulators, which may reflect the deregulated gene expression programs that underlie malignant transformation. One of the most prominent transcriptional vulnerabilities in human cancer to emerge in recent years is the bromodomain and extraterminal (BET) family of proteins, which are coactivators that link acetylated transcription factors and histones to the activation of RNA polymerase II. Despite unclear mechanisms underlying the gene specificity of BET protein function, small molecules targeting these regulators preferentially suppress the transcription of cancer-promoting genes. As a consequence, BET inhibitors elicit anticancer activity in numerous malignant contexts at doses that can be tolerated by normal tissues, a finding supported by animal studies and by phase I clinical trials in human cancer patients. In this review, we will discuss the remarkable, and often perplexing, therapeutic effects of BET bromodomain inhibition in cancer.